Farmer-participatory evaluation of mechanized dry direct-seeding technology for rice in northeastern Thailand - Sansen, Kanlaya; Wongboon, Waraporn; Jairin, Jirapong; Kato, Yoichiro (Informa UK Limited, 2019)
Rice technologies that are designed to reduce risks due to climate variations, improve productivity, or overcome labor scarcity are important in tropical Asia. The objective of this study was to evaluate mechanized options for dry direct-seeding of rice in terms of the productivity and production costs in rainfed lowlands. In a series of on-farm research trials over 3 years in Ubon Ratchathani province, Thailand, we compared seeding by seed drills mounted on two-wheel tractors with manual broadcast seeding. Demonstration trials of seed drills and site-specific nutrient management in 2017 with 11 of 26 participating farmers produced 2.50 t ha−1 of grain yield, but unexpected heavy storms forced the other 15 farmers to switch from dry to wet direct-seeding or manual transplanting. The seed drills produced 32% higher grain yield than manual broadcast seeding (3.3 vs. 2.5 t ha−1) in 2014, and 14–24% higher yield (3.3–3.6 vs. 2.9 t ha−1) in 2015. Mechanized seeding enabled seeding rate reduction by 50% in 2014 and by 52–61% in 2015, resulting in lower production costs than with manual seeding. Our results suggest that mechanized dry direct-seeding of rice with improved nutrient management can enhance farmer livelihoods in rainfed environments in northeastern Thailand. This approach can significantly reduce production costs compared with manual transplanting, while maintaining or increasing productivity compared with conventional manual broadcast seeding.